The importance of sex-disaggregated and gender data to a gender-inclusive COVID-19 response in the aquatic food systems - Choudhury, Afrina; Rajaratnam, Surendran; McDougall, Cynthia (Routledge, 2022)
The chapter underscores the importance of sex-disaggregated data and gender data for inclusive and evidence-informed fisheries and aquaculture policies and development programs.